2018
DOI: 10.1177/1477370818819689
|View full text |Cite
|
Sign up to set email alerts
|

Italian adolescents’ experience of unwanted online attentions: Recognizing and defining behaviours

Abstract: For young people, in addition to positive experiences, there are risks and negative consequences in the usage of the Internet and Information and Communication Technologies (ICT), such as forms of online harassment. At present, there is an open debate regarding the definition and issues concerning the nature of cyberspace, given the different ways that the scientific community and the general public express this phenomenon (for example, cyber-bullying, cyber-aggression, cyber-harassment). The present research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…While the perspective of some law enforcement agencies and researchers within this review indicated that digital harms should not be criminalised (Broll and Huey, 2015;Harper, 2019), it is also important to recognise it as a pathway to more serious offending (De Fazio et al, 2020;Goldsmith and Wall, 2019;Popham, 2018). Empowering cybercrime units to engage in investigative hacking may shrink the gap between rapidly evolving youth criminal methods and law enforcement, potentially involving partnering with federal agencies under new legislation (Surveillance Legislation Amendment [Identify and Disrupt] Bill 2021, 2021, Cth).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While the perspective of some law enforcement agencies and researchers within this review indicated that digital harms should not be criminalised (Broll and Huey, 2015;Harper, 2019), it is also important to recognise it as a pathway to more serious offending (De Fazio et al, 2020;Goldsmith and Wall, 2019;Popham, 2018). Empowering cybercrime units to engage in investigative hacking may shrink the gap between rapidly evolving youth criminal methods and law enforcement, potentially involving partnering with federal agencies under new legislation (Surveillance Legislation Amendment [Identify and Disrupt] Bill 2021, 2021, Cth).…”
Section: Discussionmentioning
confidence: 96%
“…Digitally assisted crime refers to traditional criminal activities carried out either with the assistance of or migration to the online space. Examples would include threats, coercion to participate in online sexual activity or non-consensual sharing of explicit content, physical assault recorded and distributed online or financial or identity fraud (Brewer et al , 2020; Broll and Huey, 2015; Choi et al , 2017; De Fazio et al , 2020). Digitally dependent crime includes hacking, online media piracy, theft of virtual objects such as video game content or cryptocurrency and online service or website disruption, known as distributed denial of services attacks (Chen et al , 2021; Cimpanu, 2016; Collier et al , 2020; Holt and Bossler, 2016; Marotta, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Novo et al (2014) found 18.2% of their sample had engaged in cyber stalking, with males more likely to engage in this behaviour. Similarly, De Fazio et al (2020) found that 12% of respondents had been a victim of cyber-stalking, though 52% acknowledged perpetration, which may suggest a difference in perception of such behaviour between victims and perpetrators, particularly when using self-report methodology. At a lower rate, Marcum et al (2014) found that 5% of adolescents had engaged in repeated online contact even after an individual had asked them to stop, noting that low self-esteem and deviant peer association were positively correlated with cyber-stalking.…”
Section: Methodsmentioning
confidence: 99%
“…Offline assaults recorded and shared online are also digitally assisted crimes, though less common. The act of “happy slapping” involves perpetrators filming themselves physically assaulting a victim and sharing the video online for self-promotion or victim-shaming (Álvarez-García, Núñez, et al , 2017; De Fazio et al , 2020), with a prevalence of 2.4% according to a Spanish study of 3,175 youth aged 12–18 years (Álvarez-García et al , 2017). This is an instance where the criminal component takes place in the traditional crime landscape, but contains a digital component which is less visible to law enforcement and may also be a motivator to engage.…”
Section: Digitally Assisted Crimementioning
confidence: 99%
“…A study in Israel of over 5,000 youth aged 9–14 found that 97% of participants used WhatsApp and that this was the most common forum for cyberbullying (Aizenkot, 2020). Cyberbullying can involve shaming or mocking a peer, repeatedly sending aggressive comments, “flooding” with nonsense or spaces to prevent the victim from participating in a chat or excluding from chats or groups (Al Hosani et al , 2019; De Fazio et al , 2020; Harper, 2019). Doxing, the publication of personal information or the “outing” of an anonymous user (Al Hosani et al , 2019), is another form of cyberbullying.…”
Section: Digital Harmmentioning
confidence: 99%